REGULATION OF ONLINE PLATFORMS, INTERMEDIARIES, AND MARKETS IN THE EUROPEAN UNION AND CHINA: Received: 8th June 2023; Revised: 2nd July 2023, 19th July 2023; Accepted: 26th July 2023 - Ramaswamy, M.P. (PEOPLE: International Journal of Social Sciences, 2023)
The EU and the PRC have recently introduced new regulatory standards governing specific online platforms, intermediaries, and markets. As an agenda to enhance digital governance, regulatory initiatives have been made on various frontiers governing digital services and digital markets to enhance both domestic and cross-border online transactions. These developments arguably enhance the relevance of the evolving European and Chinese regulatory frameworks as a stimulating subject for comparative law studies. The present paper examines the evolving key regulatory standards governing digital services and markets in Europe and the PRC and assesses their effectiveness in enhancing digital governance. The paper examines the specific regulations governing online platforms, intermediaries, and digital markets to determine the interests, obligations, and liabilities of key stakeholders. The paper assesses the effectiveness of newly introduced market regulatory standards to protect businesses and end users from the dominance of key online players. The paper argues the need for other key jurisdictions, including China, to rejuvenate their domestic digital regulatory framework with reference to the evolving European regulatory standards. The paper concludes with an analysis based on the key findings of the paper and points out the referential utility of the European experience for prospective legal harmonization needs.